(untitled) (Prostor, 2022)
Urban sprawl is a global phenomena in which a city expands and suffocates its surrounding countryside. These two indivisible entities coexist in a field that juxtaposes and composes urban and rural traits according to their respective modalities. Sociologically rural and economically urban, N’Gaous orchard city par excellence, located in the heart of the Aures and characterized by its apricot trees, has experienced an astounding spatial expansion over the last 60 years, establishing a strong presence in its territory, solidifying its service, and reaffirming its attraction. Its land area expanded by more than ten times (from 33.7 to 379.7 hectares), while the population increased by more than six times (from 4,887 to 33,515 persons ). The fast growth of its urban sprawl creates a number of issues, the most serious of which are these peri-urban orchards. The goal of this article is to investigate urban growth and urbanization in N’Gaous, Algeria. The purpose is to ascertain the effects of urban expansion on peri-urban agricultural land, the primary economic activity in the area, and to chart its evolution. Accordingly, the article employs an analytical approach to assess the agronomic potential of soils in order to quantify and monitor the agricultural potential consumed by the construction. This method is supported by the use of Geographic Information Systems as a decision support tool for spatializing the city’s growth. The focus of the article is not merely to avoid urban expansion, but to achieve the optimal agri-urban balance feasible. Hence, it will serve as a demonstration that the urban future is fashioned with the inherent potential to guide growth via the use of land assets.